2022
DOI: 10.1016/j.ijcard.2022.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation during COVID-19 pandemic: An optimized model to relieve healthcare system overload

Abstract: Background The coronavirus 2019 (COVID-19) pandemic upset healthcare systems and their logistics worldwide. We sought to assess safety and effectiveness of an optimized logistics for transcatheter aortic valve implantation (TAVI) pathway developed during the COVID-19 pandemic. Methods This is a retrospective analysis. An optimized TAVI logistics based on performing TAVI work-up and procedure during the same hospitalization was used during the COVID-19 pandemic. In-hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…However, although one may expect a prolonged length of hospital stay, several studies have shown that the LoS in TAVI patients was either comparable or shorter during the COVID-19 pandemic compared with the pre-pandemic period. 23–27 Thus, we may only speculate that the pandemic itself had an effect on the TAVI LoS and outcomes in patients in either phase.…”
Section: Discussionmentioning
confidence: 98%
“…However, although one may expect a prolonged length of hospital stay, several studies have shown that the LoS in TAVI patients was either comparable or shorter during the COVID-19 pandemic compared with the pre-pandemic period. 23–27 Thus, we may only speculate that the pandemic itself had an effect on the TAVI LoS and outcomes in patients in either phase.…”
Section: Discussionmentioning
confidence: 98%
“…More than 6 million people have died of the disease, and the number of confirmed cases is more than 540 million as of June 2022. 1 The healthcare system has been overloaded, 2 , 3 and many people have experienced financial hardship 4 , 5 and depression. 6 …”
Section: Introductionmentioning
confidence: 99%
“…More than 6 million people have died of the disease, and the number of confirmed cases is more than 540 million as of June 2022. 1 The healthcare system has been overloaded, 2,3 and many people have experienced financial hardship 4,5 and depression. 6 Thirteen COVID-19 vaccines have been developed, 7 and some (i.e., those manufactured by Pfizer-BioNTech, Moderna, and Janssen) have been approved by the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…The manuscript by Reddavid et al in this Journal [ 8 ], together with other reports from different countries [ 7 , 9 , 10 ], clearly illustrates how the healthcare system may be readjusted to react to the pandemic adversities. In all cases, efforts were addressed to the following goals: 1) keeping an acceptable waiting period for symptomatic subjects; 2) reducing total hospitalization length; 3) minimizing or even eliminating the need for post-intervention transfer to intensive care unit (ICU), which at times had also been converted into COVID ICUs.…”
mentioning
confidence: 99%